Zinc oxide piezoelectric nano-generators for low frequency applications. (15th May 2017) - Nour, E S; Nur, O; Willander, M
Abstract: Piezoelectric Zinc Oxide (ZnO) nanogenerators (NGs) have been fabricated for low frequency (<100 Hz) energy harvesting applications. Different types of NGs based on ZnO nanostructures have been carefully developed, and studied for testing under different kinds of low frequency mechanical deformations. Well aligned ZnO nanowires (NWs) possessing high piezoelectric coefficient were synthesized on flexible substrates using the low temperature hydrothermal route. These ZnO NWs were then used in different configurations to demonstrate different low frequency energy harvesting devices. Using piezoelectric ZnO NWs, we started with the fabrication of a sandwiched NG for a handwriting enabled energy harvesting device based on a thin silver layer coated paper substrate. Such device configurations can be used for the development of electronic programmable smart paper. Further, we developed this NG to work as a triggered sensor for a wireless system using footstep pressure. These studies demonstrate the feasibility of using a ZnO NWs piezoelectric NG as a low-frequency self- powered sensor, with potential applications in wireless sensor networks. After that, we investigated and fabricated a sensor on a PEDOT: PSS plastic substrate using a one-sided growth and double-sided growth technique. For the first growth technique, the fabricated NG has been used as a sensor for an acceleration system; while the fabricated NG by the second technique works as an anisotropic direction sensor. This fabricated configuration showed stability for sensing and can be used in surveillance, security, and auto-Mobil applications. In addition to that, we investigated the fabrication of a sandwiched NG on plastic substrates. Finally, we demonstrated that doping ZnO NWs with extrinsic elements (such as Ag) will lead to the reduction of the piezoelectric effect due to the loss of crystal symmetry. A brief summary into future opportunities and challenges is also presented.